Hotel’s end users preferences on green hotel attributes : an application of the quality function deployment - Monteiro, Lurdes Inês Nunes (2020)
Hotels have been suffering environmentally friendly pressure since customers are increasingly demanding more hotel green attributes. In order to identify which green attributes hotel end-users are positively perceived and how can the hotel meet the customer’s demand, this study, through the construction of a House of Quality, aims to identify which green features hoteliers should focus, without jeopardizing service quality. This research develops the Quality Function Deployment tool, House of Quality, since it establishes relationships between the hotel end-users’ ratings and the green hotel design features that fulfill the customer desires. By implementing a qualitative research methodology, the hotel customer’s preferences were analyzed through a survey. The data was collected through a questionnaire and it focused solely on the city of Porto, Portugal. Findings reveal that hotel end-users perceive as more important the attribute “Active system to detect and repair water leakage in toilets, sinks and showerheads”, followed by the implementation “Good sanitation practices (such as saving water)”. On the other hand, the “Change of bedsheets only upon request (option for multiple night guests)” and the “Use of low-flow toilets and sinks” were the least favorably perceived attributes. The HOQ construction reveals that hotels should prioritize the implementation of a program of “Waste reuse and recycling” and “Use of energy efficiency techniques and technologies”.